Viral Gastroenteritis: Sickness Symptoms and Behavioral Responses - Arash Hellysaz; Magdalena Neijd; Timo Vesikari; Lennart Svensson; Marie Hagbom (mBio, 2023)
ABSTRACT Viral infections have a major impact on physiology and behavior. The clinical symptoms of human rotavirus and norovirus infection are primarily diarrhea, fever, and vomiting, but several other sickness symptoms, such as nausea, loss of appetite, and stress response are never or rarely discussed. These physiological and behavioral changes can be considered as having evolved to reduce the spread of the pathogen and increase the chances of survival of the individual as well as the collective. The mechanisms underlying several sickness symptoms have been shown to be orchestrated by the brain, specifically, the hypothalamus. In this perspective, we have described how the central nervous system contributes to the mechanisms underlying the sickness symptoms and behaviors of these infections. Based on published findings, we propose a mechanistic model depicting the role of the brain in fever, nausea, vomiting, cortisol-induced stress, and loss of appetite.